The epidemiology of sickle cell disease in children recruited in infancy in Kilifi, Kenya: A prospective cohort study - Uyoga, S; Macharia, AW; Mochamah, G; Ndila, CM; Nyutu, G; Makale, J; Tendwa, M; Nyatichi, E; Ojal, J; Otiende, M; Shebe, M; Awuondo, KO; et al. (Elsevier, 2019)
Background: Sickle cell disease is the most common severe monogenic disorder in humans. In Africa, 50–90% of children born with sickle cell disease die before they reach their fifth birthday. In this study, we aimed to describe the comparative incidence of specific clinical outcomes among children aged between birth and 5 years with and without sickle cell disease, who were resident within the Kilifi area of Kenya.